Fabric forming simulation and process optimisation for composites - Chen, Shuai (2016)
The development and optimisation of automated fabric preforming processes is critical for the adoption of composite materials for low cost, high volume applications. This thesis presents the development of a numerical material model to simulate the forming of 2D fabric plies into complex 3D shapes. The material model has been used to evaluate the feasibility of using matched-tool forming and double diaphragm forming, to manufacture low cost fabric preforms suitable for liquid moulding processes. The research has focused on two main aspects: (I) fabric characterisation and modelling and (II) process simulation and optimisation. The forming behaviour of woven fabrics and non-crimp fabrics (NCF) has been investigated to understand the deformation mechanisms and the cause of defects, in order to seek feasible solutions for defect reduction. A non-orthogonal constitutive relation has been developed to capture the nonlinear material behaviour, which was implemented in an explicit finite element model and used to refine the forming process. Results from the material model indicate that pillar stitched NCFs are not as compliant as woven fabrics of the same areal mass. The likelihood of defects is therefore higher for the NCF and the shear behaviour is axisymmetric due to the influence of the stitch yarn. The NCF material exhibits two types of wrinkling during matched tool forming; out-of-plane wrinkling at the ply level (macro-scale wrinkling) induced by excessive shear, and in-plane wrinkling at the bundle level (meso-scale wrinkling) caused by fibre compression. Stitch rupture can also occur at high shear angles, which can lead to further localised wrinkling. Fabric bridging is the dominant defect in large curvature regions when using double diaphragm forming (DDF), and wrinkling was found to be generally lower than in matched-tool forming. The model has been used to successfully identify the cause of all of these defects in NCF preforms manufactured by DDF, and has been used to optimise preform geometry and process parameters to mitigate these problems. Darts were added to preforms to alleviate fabric bridging and improve surface conformity, using the tensile stress in the yarns to identify suitable positions and orientations, minimising the effect on the mechanical performance of the component. An optimisation methodology has been developed for placing local inter-ply stitches on multi-ply preforms, by coupling the FE analysis with a genetic algorithm. The stitches enable multiple plies to be joined together to aid robotic handling and the optimisation routine ensures that the placement of the stitches does not adversely affect the formability of the preform. Results indicate that whilst the inter-ply stitches affect the shear distribution at a global level, the formability of a multi-ply preform can be improved compared to the unstitched counterpart by optimising the pattern of through-thickness stitches. A two-step optimisation method was also developed to optimise the boundary conditions for a matched tool forming scenario. Spring-loaded clamps were used to provide in-plane tension in the fabric plies during forming, rather than using a blank holder to induce tension through friction, providing an opportunity to reduce preform size and therefore waste. The optimisation algorithm was used to determine the location and size of the clamps around the blank perimeter and the stiffness of the attached springs. It was shown that this method can effectively homogenise the global shear angle distribution, reducing the peak shear angle compared to using a segmented blank holder.